2019
DOI: 10.1002/art.40736
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Interleukin‐22– and Granulocyte–Macrophage Colony‐Stimulating Factor–Expressing, but Not Interleukin‐17A–Expressing, Group 3 Innate Lymphoid Cells in the Inflamed Joints of Patients With Spondyloarthritis

Abstract: Objective Clinical trials of the anti–interleukin‐17A (anti– IL ‐17A) antibody secukinumab have demonstrated a crucial role of the cytokine IL ‐17A in the pathogenesis of spondyloarthritis (SpA); however, its cellular source in this condition remains a matter of controversy. Group 3 innate lymphoid cells ( ILC 3s) have been recently identified as potent producers of proinflammatory cytokines, including I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Group 3 ILCs were another cell type that has been reported as a potential source of IL-17A in PsA SF (15). However, a recent study showed that although these group 3 ILCs are expanded in inflamed arthritis joints, they have failed to express IL-17A upon in vitro stimulation (16). These findings are similar to our observations with regard to CD8+ T cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Group 3 ILCs were another cell type that has been reported as a potential source of IL-17A in PsA SF (15). However, a recent study showed that although these group 3 ILCs are expanded in inflamed arthritis joints, they have failed to express IL-17A upon in vitro stimulation (16). These findings are similar to our observations with regard to CD8+ T cells.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is still not clear which of the above cell types is the main producer of IL-17A in local joints affected with PsA. Recently, it was reported that ILC3s fail to express IL-17A upon in vitro stimulation in joints affected with spondyloarthritis (16). Nevertheless, direct ex vivo comparison of IL-17A production upon T cell receptor (TCR) activation by CD4+ and CD8+ T cells has yet to be performed using PsA SF specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GM-CSF-producing ILC3s were also found to be expanded in the synovial tissue of SpA patients [44]. Consistently, a very recent study confirmed NKp44 + ILC3s were accumulated in the inflamed joints of peripheral SpA patients [45]. Although expression of Th17 signature transcripts such as RORC, AHR, and IL-23R were identified in a large proportion of synovial tissue ILC3s, these cells produce IL-22 and GM-CSF but not IL-17, suggesting they are not a significant source of IL-17 in SpA [45].…”
Section: Spondyloarthritissupporting
confidence: 67%
“…The numbers of ILC1 and ILC3 have been reported to be increased in the peripheral blood, synovial uid, and lymph node in patients with RA and juvenile idiopathic arthritis (JIA) [21,22], whereas the number of peripheral ILC2 was decreased [23]. On the other hand, ILC3 has been shown to be present in the healthy entheses and perientheseal bone and expand in the peripheral blood, gut, synovial uid, or bone marrow in SpA patients and produce key in ammatory cytokines related to SpA [24][25][26][27][28][29]. Although these reports indicate that ILCs are involved in the pathophysiology of RA and SpA, the associations between ILCs and the patterns of musculoskeletal in ammation are unknown.…”
Section: Introductionmentioning
confidence: 99%